El bien común político en «Natural Law and Natural Rights» en cotejo doctrinal con el tomismo - Castaño, Sergio Raul (2020)
This article deals, first of all, with the analysis ofthe notion of common good and political common good,as it is proposed by John Finnis in Natural Law and NaturalRights. Then, in a second moment, the paper aims tocontrast this conception with the doctrine held by Aquinasand some outstanding contemporary Thomists, until1980.The scientific-philosophical question about the systematicvalidity, «in the things themselves» (Husserl), that it is possibleto recognize both one and the other, remains opento debate.